The Application of Pyrrolo[2, 3-d]pyrimidine Scaffold in Medicinal Chemistry from 2017 to 2021 - Liang, Ting; Yang, Yingxiang; Wang, Jiayun; Xie, Zhao; Chen, Xin (Mini Reviews in Medicinal Chemistry, 2023)
The application of privileged structures in drug design is an effective strategy, which usually leads to innovative hits/leads and successful structural optimization. Pyrrolo[2, 3- d]pyrimidine are such a scaffold which are frequently used in many clinical drugs. The biocompounds bearing pyrrolo[2, 3-d]pyrimidine skeleton show different pharmacological effects such as anti-neurodegenerative, anti-inflammatory, antibacterial, and antitumor activities. In this article, we reviewed the representative structures and biological characteristics of reported synthetic pyrrolo[2, 3-d]pyrimidine compounds from 2017 to 2021. The linked diseases and targets were also mentioned briefly. This work might provide a reference for the subsequent drug discovery based on pyrrolo[2, 3-d]pyrimidine scaffold.
Keywords: IKKs